2022
DOI: 10.1111/imj.15354
|View full text |Cite
|
Sign up to set email alerts
|

Opioids in advanced lung malignancy: a clinical audit of opioid prescription, patient education and safeguarding

Abstract: Background Opioids have an important role in symptom management for people with advanced cancer. Clinical guidelines recommend patient education to ensure the safe use of opioids; however, no Australian studies have explored current education and safeguarding practices when opioids are initiated to advanced cancer patients. Aims To investigate risk assessment, safeguarding and education practices when opioids are first prescribed to advanced lung cancer patients. Methods A retrospective medical record audit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Building evidence-based approaches for managing co-occurring opioid and nonmedical stimulant use is important in cancer care, given the high rates of stimulant use and ubiquity of prescription opioids. 1,2 Clinicians who treat cancer pain with opioids regularly encounter nonmedical stimulant use (i.e., methamphetamine, cocaine), yet there is little evidence-based management guidance. 3,4 Among people with cancer who receive urine toxicology testing, nonmedical stimulant use is the second most common unexpected substance detected on urine screening after cannabis.…”
Section: Introductionmentioning
confidence: 99%
“…Building evidence-based approaches for managing co-occurring opioid and nonmedical stimulant use is important in cancer care, given the high rates of stimulant use and ubiquity of prescription opioids. 1,2 Clinicians who treat cancer pain with opioids regularly encounter nonmedical stimulant use (i.e., methamphetamine, cocaine), yet there is little evidence-based management guidance. 3,4 Among people with cancer who receive urine toxicology testing, nonmedical stimulant use is the second most common unexpected substance detected on urine screening after cannabis.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the possible barrier, NPs may benefit from guideline-based training on how to communicate about common opioid-related adverse effects and potential long-term harm with patients. As a separate issue, patient education tends to be underreported in medical records compared with other aspects of medical care, so it is uncertain how much NPs are currently educating patients about opioids (Anil et al, 2021). Therefore, additional research is needed on NPs' practices with respect to patient education on opioids.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Merlin et al 6 provide expert consensus on opioid management in people receiving medication treatment for OUD who have co-occurring cancer-related pain. Anil et al 15 reported no association between opioid risk counseling and opioid initiation; however, specialty may influence opioid decision-making documentation, with palliative care clinicians noted to be 8 times more likely to document opioid education than medical oncologists. Collectively, the studies give information on provider-specific and patient-specific factors that may inform opioid-prescribing decisions in people with cancer.…”
Section: Introductionmentioning
confidence: 99%